Epidemic Outbreak of Mealy-bug Ferrisiana virgata (Cockerell) (Pseudococcioae : Homoptera) in Su-babul (Leucaena leucocephala (lam) De Wit.) Plantations - Madhavan Pillai, S. R.; Gopi, K. C. (Indian Forester, 1990)
A recent case of epidemic outbreak of mealy-bug Ferrisiana virgata (Cockerell) as a pest of Leucaen leucocephala is reported in this paper.